Dust abundance and grain size in galaxy halos. (April 2020) - Hirashita, Hiroyuki; Lin, Chih-Yu
Abstract: We investigate the abundance and properties (especially, grain size) of dust in galaxy halos using available observational data in the literature. There are two major sets of data. One is (i) the reddening curves at redshifts z ∼ 1 and 2 derived for Mg ii absorbers, which are assumed to trace the medium in galaxy halos. The other is (ii) the cosmic extinction up to z ∼ 2 mainly traced by distant background quasars. For (i), the observed reddening curves favor a grain radius of a ∼ 0.03 μ m for silicate, while graphite is not supported because of its strong 2175 Å bump. Using amorphous carbon improves the fit to the reddening curves compared with graphite if the grain radius is a ≲ 0.03 μ m. For (ii), the cosmic extinction requires η ≳ 10 − 2 ( η is the ratio of the halo dust mass to the stellar mass; the observationally suggested value is η ∼ 10 − 3 ) for silicate if a ∼ 0.03 μ m as suggested by the reddening curve constraint. Thus, for silicate, we do not find any grain radius that satisfies both (i) and (ii) unless the halo dust abundance is much larger than suggested by the observations. For amorphous carbon, in contrast, a wide range of grain radius ( a ∼ 0.01 −0.3 μm) is accepted by the cosmic extinction; thus, we find that a grain radius range of a ∼ 0.01 –0.03 μm is supported by combining (i) and (ii). We also discuss the origin of dust in galaxy halos, focusing on the importance of grain size in the physical mechanism of dust supply to galaxy halos.